A novel meteorological sensor data acquisition approach based on unmanned aerial vehicle. (2018) - Li, Chuanlong; Sun, Xingming
Meteorological sensor data acquisition is critical for various applications and researches. Currently, meteorological sensor data monitoring and acquisition mainly relies on the automatic weather station (AWS), wireless sensor network, satellites, and airborne remote sensing, etc. However, these conventional methods have some insuperable deficiencies. Recent advances in the unmanned aerial vehicle (UAV) for scientific use make drones easily overcome some of the paucity generated by these means. UAV as a sensor bearing platform can be used to collect sensor data in a more responsive, timely, three dimensional, and cost-effective manners. By implementing sensor network alike methods, drones can simulate the mobile ad-hoc networks in a mission and reduce the communication energy cost between each sensor node. This paper first demonstrates the feasibility of this approach, then proposes a sensor bearing framework aiming to bridge UAV remote sensing technique and customised meteorological sensor. A system prototype is developed and some real-world field tests indicate the application of the proposed framework is practical.